Integrated Ultrasound Assessment of the ’Placenta-Brain Unit’: Correlating Uteroplacental Doppler with Fetal Neurosonography Findings in Diabetic Pregnancies - Riyadh Adel Jaed (Journal of Biomedicine and Biochemistry, 2025)
Objective:To investigate the relationship between utero-placental Doppler indices and detailed fetal neurosonographic findings in pregnancies complicated by pre-gestational and gestational diabetes mellitus (GDM). Methods:A prospective cohort study was conducted on 150 diabetic pregnancies (75 pre- gestational, 75 GDM) and 75 matched healthy controls between 28-32 weeks of gestation. All participants underwent pulsed-wave Doppler assessment of the uterine arteries (UtA) to determine the pulsatility index (PI) and the presence of an early diastolic notch. Subsequently, a dedicated fetal neurosonography was performed to measure the transcerebellar diameter (TCD), Sylvian fissure depth, and lateral ventricle width, and to assess the development of the corpus callosum and cortical sulcation. Results: The diabetic cohort, particularly the pre- gestational subgroup, demonstrated significantly higher mean UtA-PI values and a higher prevalence of bilateral notching compared to controls (p < 0.01). Neurosonography revealed significant alterations in the diabetic groups, including a larger transcerebellar diameter (p < 0.05), abnormal Sylvian fissure maturation, and delayed opercularization compared to the control group (p < 0.01). A significant inverse correlation was observed between UtA-PI and transcerebellar diameter (r = -0.45, p < 0.001), and a positive correlation with Sylvian fissure depth (r = 0.52, p < 0.001) in the pre-gestational diabetes group. Conclusion: This study demonstrates a significant correlation between impaired utero-placental hemodynamics and alterations in fetal brain development in diabetic pregnancies, supporting the concept of a "placenta-brain unit". Integrated ultrasound assessment of this unit may serve as an early biomarker for identifying fetuses at risk for neurodevelopmental morbidity, enabling potential early intervention strategies.